2003
DOI: 10.1155/s1023621x03000393
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics in Torque Converters: Validation and Application

Abstract: This article describes some of the computational fluid dynamics (CFD) work being done on three-element torque converters using a commercially available package CFX TASCflow. The article details some of the work done to validate CFD results and gives examples of ways in which CFD is used in the torque-converter design process. Based on the validation study, it is shown that CFD can be used as a design and analysis tool to make decisions about design direction. Use of CFD in torque converters is a developing fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…They concluded that the main reasons for this increase in torque ratio were the increased stator exit angle and decreased stator losses. Schweitzer and Gandham [10]had described some of the work done to validate CFD results and gave examples of ways in which CFD is used in the torque converter design process. Based on the validation studies, they concluded that CFD could be used as a design and analysis tool for torque converter development.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the main reasons for this increase in torque ratio were the increased stator exit angle and decreased stator losses. Schweitzer and Gandham [10]had described some of the work done to validate CFD results and gave examples of ways in which CFD is used in the torque converter design process. Based on the validation studies, they concluded that CFD could be used as a design and analysis tool for torque converter development.…”
Section: Introductionmentioning
confidence: 99%
“…The study [9] shows an evaluation of the possibilities to use an a typical working fluid (a mixture of oil and air) within a partially filled HC, on the basis of numerical 3D calculations and experimental research. Schweitzer and Gandham [10] conducted an analysis of a working fluid flow within the HTC using CFD methods, and the results of the numerical calculations are verified on a test station using laser Doppler velocimetry LDV. Similar research is shown in the studies [11,12,13,14,15,16,17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The transmission system model includes a torque converter model, an automatic transmission model and a final drive model. The torque converter model and automatic transmission model are based on [24][25][26] and [27,28], respectively. The variables of the vehicle model are shown in the following Table 1.…”
Section: Structure Of Vehicle Dynamics Modelmentioning
confidence: 99%